Gold from Marigold Impact of marigold demonstrations under Farmer FIRST Programme - Arora, R K; Sharma, Pawan Kumar; Kumar, Parveen; Singh, Rajbir (Indian Farming, 2021)
Agriculture in India is dominated by marginal and small farmers constituting 86% of the community as per the Agriculture Census 2010-11. For a vast majority of the farming population in the country, agriculture is related to only growing food crops like wheat, paddy, maize, fodder crops like Barseem, Jowar, Bajra for animals and pulses if the land holding permits. The farmers have been carrying out this mono cultural legacy over the generations. In the present era, a lot of inputs from seed to chemical fertilizers to plant protection chemicals including weedicides are required for growing different crops, which increases cost of cultivation. The cost is further escalated by the labour and machinery charges incurred while performing different operations in the fields. Ultimately, it results in a situation where the cost of cultivation exceeds the output. This is basically the reason why the farming is considered as a non-remunerative enterprise. The problems becomes more severe in case of small and marginal farmers who find it difficult to bear the brunt of increased cost escalation and are left with no option except to quit agriculture. This ‘quit agriculture’ movement has already been recognized at national level.